2013
DOI: 10.1111/jfb.12063
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in δ15N signature following the onset of exogenous feeding in rainbow trout Oncorhynchus mykiss: importance of combining length and age data

Abstract: The δ(15) N isotopic change of recently emerged rainbow trout Oncorhynchus mykiss due to diet shift from yolk sac to exogenous feeding was evaluated in a field study. The fit of a general model including both fish length and age in days as co-variables indicates that the specific δ(15) N of individual fish at any given time along the ontogeny is determined by its growth trajectory. The results suggest that estimations based on fish size alone could bias data interpretation and maternal origin determinations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…That reversal of typical sizeδ 15 N relationships presumably reflects maternal provisioning of eggs with nitrogen that had already been isotopically enriched substantially by serial trophic fractionation. Such shifts early in ontogeny have been reported in fish (Liberoff, Riva Rosso, Fogel, Ciancio, & Pascual, 2013;Post, 2003) and other animals (Jenkins, Partridge, Stephenson, Farley, & Robbins, 2001) as the provenance of tissue nutrients transitions from maternal investment to an independent diet. In young pike, it appears that tissue turnover is sufficiently complete by a size of 20 mm to yield isotope ratios that reflect invertivory, and subsequently the onset of piscivory.…”
Section: Discussionmentioning
confidence: 61%
“…That reversal of typical sizeδ 15 N relationships presumably reflects maternal provisioning of eggs with nitrogen that had already been isotopically enriched substantially by serial trophic fractionation. Such shifts early in ontogeny have been reported in fish (Liberoff, Riva Rosso, Fogel, Ciancio, & Pascual, 2013;Post, 2003) and other animals (Jenkins, Partridge, Stephenson, Farley, & Robbins, 2001) as the provenance of tissue nutrients transitions from maternal investment to an independent diet. In young pike, it appears that tissue turnover is sufficiently complete by a size of 20 mm to yield isotope ratios that reflect invertivory, and subsequently the onset of piscivory.…”
Section: Discussionmentioning
confidence: 61%
“…First, introduced rainbow trout in Patagonia and the Santa Cruz River have widely varying physiological, behavioral, and life‐history responses to environmental variables (e.g., Liberoff et al, 2013, 2014, 2015, 2019). To what extent fish from each ancestral source contributed to the basis and genetic legacy of Santa Cruz River fish is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated frequencies of the Omy5 ancestral haplotype in the Santa Cruz River populations do not indicate a clear association with anadromy, but this may be confounded by the variable association of the Omy5 inversion with migratory life history, temperature, and development rate (Nichols et al, 2008; Pearse & Garza, 2015; Pearse et al, 2019). Evidence from a study of the early phases of growth revealed that the expression of anadromy in the Santa Cruz River is linked to fast growth during the first year of life, whereas residency is associated with slow growth, suggesting that alternative forms within this river may result from a body size–based threshold for life‐history determination (Liberoff, 2013; Liberoff et al, 2013, 2014; Riva Rossi, 2004). In the introduced range, the fitness value of a tactic for a given condition could be very different from the value in the native range and could also vary along the environmental gradient of Patagonia, resulting in differences in the body size for which anadromy conferred greater advantages and was selected for in the native range (Riva Rossi, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotope (such as 13 C and 15 N) ratios can be used to determine nutrient sources in natural food webs [20][21][22]. Stable nitrogen isotope analysis has also been used in marine and freshwater environments, primarily to investigate diet switching by and trophic level shifts of fish communities [23,24]. It also has been used in aquaculture ecosystems to quantify the relative importance of various natural food resources in the diet of fish [25].…”
Section: Introductionmentioning
confidence: 99%